Using of Marinades in Cooking Technologies of Main-Course Dishes - Tatsenko, Olexiy; Holikova, Tatiana; Smirnova, Elizabeth (My University, 2014)
The objective of this study is to investigate technological properties of grilled meat stakes. The thermal losses and duration of cooking to the readiness of beef, pork, mutton and veal stakes have been evaluated. The impact of vinegar- and oil-based marinades on this process has been studied. The recipe of marinade with kefir and kiwi fruit has been proposed. Kiwi contains food organic acid that leads to softening of meat and kefir is probiotic product that increases the food value of ready meal. It has been founded that such a marinade has the highest degree of absorption by the product. The caloric value of ready-made dishes has been calculated. Recommendations on further using of marinades in the sphere of restaurant business have been offered.
Keywords: meat dishes; marinade; м’ясні страви; мясные блюда; маринад; кафедра іноземних мов професійного спрямування; кафедра готельно-ресторанної справи